Selection of clones for canopy replacement in rehabilitation of vascular streak diebak in mature cocoa (Theobroma cacao L.) in Malaysia - Osman, Rozita (2013)
Vascular streak dieback (VSD) caused by the fungus Oncobasidium theobromae Talbot & Keane is a major disease of cocoa in Malaysia. In existing cocoa areas,canopy replacement using tolerant clones can be practiced for VSD control. The general objective of this study was to develop suitable canopy replacement technique for rehabilitation of VSD infected mature cocoa. Screening of VSD tolerant clones were carried out on ten selected clones and non-grafted seedling was used as the control. Based on visual observations and biochemical analysis,four clones: PBC123, KKM25, MCBC1 and QH1003 showed tolerant to VSD. These clones were low in proline content (0.99 – 1.19 μmol g-1 fresh weight), low in total polyphenols content (1.42 – 1.72 mg GAE g-1 fresh weight) and high in peroxidase activity especially PBC123 (0.58 U mg protein-1) compared susceptible clones (proline content – 1.31 – 1.60 μmol g-1 fresh weight, total polyphenols content – 3.71 – 3.95 mg GAE g-1 fresh weight, peroxidase activity – 0.20 U mg protein-1). These clones were selected for subsequent study. The graft compatibility between PBC130 and selected clones was observed and evaluated. The observations and anatomical study of four clones revealed that four selected clones: KKM25, QH1003, PBC123 and MCBC1 were compatible to be grafted to PBC130 although it was already grafted to hybrid rootstock. The possible duration required for cocoa clones graft union formation was about 40 days. These four clones were subsequently used for study in the third experiment where they were grafted to mature PBC130 at four grafting distances and four grafting points under field conditions. The VSD DSI was higher (1.432) at 1.5m grafting distances, girth of the grafted branches was smallest in 2m grafting distance (8.73 cm) and 5 grafting points (9.49 cm), stomatal conductance was higher at 1.5 m grafting distance (47.24 mmol m-2s-1), proline content and peroxidase activity were higher at 1.0 m grafting distance (1.71 μmol g-1 fresh weight and 16.84 U mg protein-1, respectively) and total polyphenols content was higher at 1.5 m grafting distance. After successful canopy replacement,cocoa production yield had increased significantly (12.75 – 18.54 pods per tree per year) compared to before its implementation (5.50 – 10 pods per tree per year). After taking few factors into considerations, it was found that grafting at 1.5m grafting distance with 3 to 4 grafting points per tree can rehabilitated VSD infected mature cocoa trees and increase cocoa production.